PENGARUH MODEL PEMBELAJARAN PASPOR (PAIRING, SQUARE, PRESENTATION, REPETITION) TERHADAP PEMAHAMAN SISWA DALAM PENULISAN PSEUDOCODE PADA MATA PELAJARAN INFORMATIKA - Putri Dewi, Lena; Jufri, Jufri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the PASPOR learning model (Pairing, Square, Presentation, Repetition) on students' understanding in pseudocode writing in Informatics subject for 10th grade students at SMA Negeri 1 Pendalian IV Koto. A pre-experimental design with one-group pretest-posttest was employed. The sample consisted of 30 students selected through purposive sampling. Data were collected using essay-based pretest and posttest instruments, student activity observation sheets, and model implementation checklists. All instruments were validated by two experts with an average validity score of 88.15% (very valid category). Results indicated that the mean pretest score of 42.17 increased to 79.83 on posttest, with a mean N-Gain of 0.62 (medium category). The paired sample t-test produced a t-value of -12.407 with 29 degrees of freedom (df = 29) and a significance value (Sig. 2-tailed) of 0.000; therefore, H₁ is accepted. Student activity was in the active category at 80.00%, and teacher implementation of the PASPOR model reached 93.75% (very good category). Therefore, the PASPOR learning model significantly affects the improvement of students' understanding in pseudocode writing.